Experimental Investigation on the Mechanical Characteristics of a Novel Hybrid Densified Wood-Filled Aluminum Tube Dowel for Timber Connections - Marie-Gabrielle Tétreault; Guillaume Rollo; Marc Oudjene; Mario Fafard (Engineering Proceedings, 2023)
The structural performance of a novel hybrid dowel, made of a densified wood-filled aluminum tube (DWFAT), for structural timber joints was investigated experimentally, for the first time. Three-point bending tests have been conducted on both hybrid DWFAT dowels and densified wood dowels (DWD) in order to evaluate their strength and stiffness characteristics as well as their ductility and failure modes. The developed hybrid DWFAT dowels were then used and tested in the context of both slotted-in aluminum plate timber and timber-to-timber double shear connections and the obtained load-slip curves as well as the failure modes were analyzed and compared to their equivalent connections made with conventional steel dowels. The results showed that the developed hybrid DWFAT dowel is promising and can be a potential substitute for conventional steel dowels.